Immunohistochemical Expression of Epidermal Growth Factor Receptor in Hepatocellular Carcinoma - Nikolova, Dafina; Chaloska, Viktorija; Genadieva Ivanova, Magdalena?; Nikolovska, Emilija; Volkanovska, Anche; Orovchanec, Nikola; Kostadinova Kunovska, Slavica; Petrushevska, Gordana; Janevska, Vesna (Macedonian Academy of Sciences and Arts/Sciendo, 2018)
Epidermal growth factor receptor (EGFR) signaling plays an important role in various cancers, including hepatocellular carcinoma (HCC). We aimed to evaluate immunoexpression of EGFR in HCC and surrounding non-tumor liver tissue and to correlate it to multiple clinicopathologic data.
Keywords: EGFR; HCC; cirrhosis; survival; immunohistochemistry